2021
DOI: 10.2147/cia.s303629
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Liver Function Tests and Their Correlation with Illness Severity and Mortality in Patients with COVID-19: A Retrospective Cohort Study

Abstract: Objective To describe the longitudinal changes in liver function tests, and their association with illness severity and mortality in patients with COVID-19. Methods A retrospective cohort study of 1003 hospitalized patients with COVID-19 was conducted. Longitudinal liver function tests and clinical outcomes were analyzed. Results Abnormal liver function parameters were observed, both at admission (ALT 13.2%, AST 8.5%, ALP 2.0%, GGT 7.4%, LDH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…There is also significant data published in the last year on liver injury caused by therapeutic drugs such as lopinavir, ritonavir, remdesivir, hydroxychloroquine and azithromycin. Drugs such as lopinavir are broken down by cytochrome P450 3A4 enzymes in hepatocytes, which may contribute to the elevated ALT and AST levels due to hepatocellular damage [ 172 ]. Antipyretic drugs containing acetaminophen at high doses used in treating COVID-19 patients can be hepatotoxic and may cause hepatocellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…There is also significant data published in the last year on liver injury caused by therapeutic drugs such as lopinavir, ritonavir, remdesivir, hydroxychloroquine and azithromycin. Drugs such as lopinavir are broken down by cytochrome P450 3A4 enzymes in hepatocytes, which may contribute to the elevated ALT and AST levels due to hepatocellular damage [ 172 ]. Antipyretic drugs containing acetaminophen at high doses used in treating COVID-19 patients can be hepatotoxic and may cause hepatocellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…As for the laboratory markers, we observed that patients who fell had higher TSH and lower ALT levels compared to those that did not fall. Research has shown that COVID-19 disease patients with more severe illness have lower TSH and higher ALT levels than those with milder illness [ 38 40 ]. Thus, higher TSH and lower ALT in patients who fell may simply be attributable to the fact that they had a milder illness and fell because they were ambulatory.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, assumed that the direct cytopathic effect of SARS-CoV-2 might not be the primary mechanism of COVID-19-associated liver damage. Liver dysfunction in COVID-19 can be associated with an uncontrolled immune reaction, sepsis, or druginduced liver injury, in addition to the direct cytopathic effect of the virus, but further monitoring is needed (Xu, et al, 2021).…”
Section: Association Of Clinical Characteristics With Post-treatment Conditions Of Covid-19 Patientsmentioning
confidence: 99%